2017
DOI: 10.1242/dev.144279
|View full text |Cite
|
Sign up to set email alerts
|

Trends in tissue repair and regeneration

Abstract: The 6th EMBO conference on the Molecular and Cellular Basis of Regeneration and Tissue Repair took place in Paestum (Italy) on the 17th-21st September, 2016. The 160 scientists who attended discussed the importance of cellular and tissue plasticity, biophysical aspects of regeneration, the diverse roles of injury-induced immune responses, strategies to reactivate regeneration in mammals, links between regeneration and ageing, and the impact of non-mammalian models on regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 55 publications
1
52
0
4
Order By: Relevance
“…The involvement of the immune system in repair had long been suspected (27–30), but it is only recently that a precise cellular and molecular characterization of this process has been possible. In this review, we describe the impact of the immune system on repair and dysregulated repair and emphasize the key role played by immune cell plasticity in repair (Figure 1) (31). The word “plasticity” is used with different and often confusing meanings.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the immune system in repair had long been suspected (27–30), but it is only recently that a precise cellular and molecular characterization of this process has been possible. In this review, we describe the impact of the immune system on repair and dysregulated repair and emphasize the key role played by immune cell plasticity in repair (Figure 1) (31). The word “plasticity” is used with different and often confusing meanings.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic of Ang II /Ang-(1-7) levels in the cell culture system was determined in this study, and according to the results (Fig. 1), we speculated that exogenous Ang II was degraded rapidly by neprilysin that is expressed in MSCs [23], at the same time, Ang II was converted into Ang- (1)(2)(3)(4)(5)(6)(7). In this process, the positive feedback phenomenon (Ang II level at 6 h time point) of Ang II [23] existed, which was abolished by ACE2 overexpression in the LV-ACE2-MSC group.…”
Section: The Ang Ii/ace2/ang-(1-7) Levels and The Cytoprotective Effectmentioning
confidence: 68%
“…Currently, the major therapies for myocardial infarction (MI) include drugs, percutaneous coronary intervention with stent implantation, trials of stem cell transplantation. Giving the great potential of self-renew and differentiation of stem cells, stem cell transplantation was expected to improve cardiac function via tissue regeneration [2,3]. Mesenchymal stem cells (MSCs) are widely used in clinical trials for MI treatment; whereas it is reported that MSCs give therapeutic benefits via paracrine of cytokines [4] more than differentiation into mature cardiomyocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rejenerasyon canlıda oluşan bir hasar sonrası fonksiyonel restorasyon sürecine verilen isimdir [33] . Canlılar farklı yenilenme kapasitesine sahip olmakla beraber, omurgalılarda yenilenme kapasitesi çoğunlukla doku düzeyinde görül-mektedir [34] .…”
Section: Discussionunclassified